OPTIMIZATION OF RICE HUSK HYDROLYSIS TIME INTO FURFURAL ASSISTED BY MICROWAVE - Marinda Rahim; Arief Adhiksana; Mina Indriani (Konversi, 2019)
Rice production in East Kalimantan is quite high. In the process of milling usually rice husk obtained is about 20-30% from grains weight produced. The quite potential amount of rice husk  has not yet widely utilized, even though rice husk contains pentosan which can be processed into furfural by hydrolysis method.  The purpose of this research is to develop one step hydrolysis technique of rice husk into furfural  with  microwaves assistance to obtain the optimum time which can produce maximum furfural. In  this research 50 grams of rice husk was added with 500 mL of H2SO4 1% as the catalyst. The mixture was then hydrolyzed using microwave-assisted method with a time variety of 15, 30, 45, 60, 75, 90, 105 and 120  minutes.  The result of analysis by Gas Chromatography (GC) showed that the highest result of furfural was at 90 minutes with a yield of 2.923%.